Internetbasierte Interventionen in der Behandlung psychischer Störungen = Internet-based interventions in the treatment of mental disorders : overview, quality criteria, perspectives - Klein, Jan Philipp; Bohus, Martin (Der Nervenarzt, 2016)
BackgroundMental disorders are frequently not or only insufficiently treated. Internet-based interventions offer the potential of closing the existing gaps in the treatment of mental disorders; however, it is very difficult for patients and providers to choose from the numerous interventions available.ObjectiveThe aim of this study was to develop a set of quality criteria that can help patients and care providers to identify recommendable internet-based interventions.MethodsA selective literature search was carried out and the existing evidence on internet-based interventions in the treatment of mental disorders was collated. A panel of experts then developed quality criteria based on existing models for the systematic assessment of telemedicine applications.ResultsInternet-based interventions are effective in the treatment of a broad range of mental disorders. The best evidence is available for depression and anxiety disorders. A set of criteria is proposed for the evaluation of available internet-based interventions using a checklist. These criteria have to be developed further with input from other stakeholders.DiscussionWhen taking these quality criteria into account, evidence-based interventions available on the internet can make an important contribution to improvement of the care of patients with mental disorders.